1999
DOI: 10.1046/j.1365-2648.1999.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

The professional socialization of diploma of higher education in nursing students (Project 2000): a longitudinal qualitative study

Abstract: This paper presents a new theory of professional socialization in relation to diploma of higher education in nursing students (Project 2000). It was derived from a 3-year, grounded theory, longitudinal study exploring the effects of supernumerary status and mentorship on students undertaking practice placements. A purposive sample of 17 students was used. Ten students volunteered to be interviewed on five separate occasions throughout their course and to keep a diary to record their experiences of mentorship d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 30 publications
2
83
0
4
Order By: Relevance
“…This was also observed by Smith whereby that the students who participated in her study would not report problems which arose in the ward because they were frightened of negatively affecting their ward reports [37]. The reward for conforming to the prevailing norms among other factors clearly includes receiving a good practical assessment [38]. There is evidence that nursing students conform and comply to gain acceptance [39].…”
Section: Discussionmentioning
confidence: 83%
“…This was also observed by Smith whereby that the students who participated in her study would not report problems which arose in the ward because they were frightened of negatively affecting their ward reports [37]. The reward for conforming to the prevailing norms among other factors clearly includes receiving a good practical assessment [38]. There is evidence that nursing students conform and comply to gain acceptance [39].…”
Section: Discussionmentioning
confidence: 83%
“…This has been cited by previous studies as a contributory factor to conflict and inhibitory to learning (Downes, 2001) and inhibitory to socialisation of the student nurse on placement (Joyce, 1998;Hyde and Brady, 2002). Nevertheless there are both positive and negative attributes to supernumerary status on clinical placement (Gray and Smith, 1999;Spouse, 2000;O' Callaghan and Slevin, 2003;McGowan, 2006). This study group were on rostered placement at the time of the study, which warrants further exploration.…”
Section: Feeling Excludedmentioning
confidence: 84%
“…Also there was concern that learning targets specific to each ward, termed 'critical elements' ward were not being met causing concern for some students. While the clinical environment is considered a good method of learning for students (Gray and Smith, 1999;Condell et al, 2001), this study has revealed that it is not without difficulties.…”
Section: Unmet Learning Needsmentioning
confidence: 99%
“…Anxiety occurs again at the end of the study (24). Anxiety at the end of the study is related to transitioning from a student to a nurse and taking full responsibility for the tasks performed.…”
Section: Methods Study Designmentioning
confidence: 99%
“…gray and smith describe the phases through which students pass through clinical practice (24). before they begin clinical practice, students experience anxiety; during practice they encounter the reality of the workplace and experience cultural shock.…”
Section: Nursing Educationmentioning
confidence: 99%